Harmony Family Time and Guided Me Time for Religious Moderation Internalization in Early Childhood: A Qualitative Case Study in East Java, Indonesia - Yuli Salis Hijriyani; M. Fathurahman; Yasothai Paramasivam (Global Educational Research Review, 2025)
Purpose – To analyze the synergy of harmony family time and guided me time for the insertion of religious moderation values in children aged 3-6 years in the era of digital disruption. Methods/Design/Approach – A descriptive qualitative case study in East Java involving 15 parents (purposive). Data were obtained through in-depth interviews, participatory observation, and documentation; analyzed thematically with source triangulation and limited member checking. Findings – 90 percent of parents provide family time at least three times per week as a space for role modeling and dialogue about respect for differences. A total of 70 percent of parents stated that children have me time for playing or reading that often repeats tolerance messages from family time. Me time remains risky because of exposure to digital content that is not age-appropriate. For this reason, 75 percent of parents curate educational content, limit duration, and conduct brief conversations after media access. Synergy appears when values from family time are reprocessed by children during me time through symbolic play or guided media. Originality/Value – This article offers a framework of family interaction rhythms that connects togetherness as a provider of value narratives and a sense of security with personal space as reflective appropriation, going beyond approaches that only focus on screen control. Practical Implications – Routine family time based on children’s daily experiences, bridges to reflective activities during me time, and active digital assistance through curation, duration limits, and brief dialogue are recommended. The alignment of tolerance messages at home and early childhood education (PAUD), as well as strengthening parents’ digital literacy, is recommended. Keywords religious moderation, early childhood, family time, me time, parents’ digital literacy. Paper type Research paper